Maximizing solar energy harvesting: enhancing the efficiency of bifacial dye-sensitized solar cells with Graphenated carbon nanotubes composites in multi-layered stacked photoanode - Lawal, Ismail; Shafie, Suhaidi; Pandey, Shyam S.; Jafaar, Haslina; Mustafa, Mohd Amrallah; Ismail, Ismayadi; Ahmad Kamarudin, Mazliana; Mohd Noor, Ikhwan Syafiq; Liu, Xinzhi; AlSultan, Hussein A.; Babani, Suleiman; Abdulhamid, Ibrahim Bako; et al. (Elsevier, 2025)
This study inaugurally delves into optimizing bifacial dye-sensitized solar cells (DSSCs) by integrating graphene-carbon nanotubes (g-CNT) into the matrix of titanium dioxide (TiO2) for application as a mesoporous semiconductor material. TiO2 nanoparticles were synthesized using a hydrothermal method and then impregnated with g-CNT at concentrations of 0.0025wt%, 0.0050wt%, and 0.0100wt%. Photoanodes were fabricated using these paste variants, and their performance was assessed. The results show that the 0.005wt% g-CNT variant notably enhances the performance of the TiO2 cell, increasing its overall power conversion efficiency (PCE) from 3.76% to approximately 4.53%, representing a 20% improvement. An innovative approach was introduced by layering a transparent TiO2 with an additional layer of the optimized composite containing the 0.005wt% g-CNT variant. This concept demonstrated a significant PCE improvement to 5.90%, enhancing the cell performance of the TiO2 variant by 56.8% and the TiO2/0.005wt% g-CNT composite variant by 27.7%. The stacked photoanode showed an intermediate band gap value of 3.11eV, promoting improved light absorption, especially on the back side where light intensity is lower. This results in reduced series resistance on the front and back side of 12.80Ω/ 13.38Ω, along with lower charge transfer resistance (Rct2) values of 7.5Ω and 5.5Ω, respectively. The decreased Rct2 indicates improved charge transfer and reduced recombination, as evidenced by more positive charge collection efficiency values recorded, particularly with backside illumination. FESEM imaging showed apparent g-CNT growth, while EDX analysis confirmed the composition of the TiO2/ g-CNT. The 2D band (sp2) presence in the Raman spectra indicated the graphitic structure of the graphene-carbon nanotubes (g-CNT). High shunt resistances and low series resistance extracted from EIS data ensure efficient charge transfer, guaranteeing superior performance of the composite together with the stacked photoanodes. This study portrays the enhanced performance of bifacial DSSCs through the use of multi-layer stacking of both TiO2(T/sp) and TiO2/ g-CNT as a novel photoanode semiconductor material, paving a new exploitation path of advancements in photovoltaic cell’s nano technology.